PT Gojek's Responsibility Towards Gocar Drivers Who Experience Work Accidents Based on Law Number 24 of 2011 Concerning the Employment Social Security Administration Agency - Peter Joshua Lumban Raja; Besty Habeahan; Sovia Febrina Tamaulina Simamora (Journal of Legal and Cultural Analytics, 2025)
The Social Security Organizing Body for Employment is a public program that provides protection for workers to address certain socio-economic risks, and its implementation uses a social insurance mechanism. The purpose of this research is to understand the responsibility of PT Gojek towards Gocar drivers who experience work-related accidents based on Law Number 24 of 2011 concerning the Social Security Organizing Body for Employment. Furthermore, this study aims to examine the mechanism used to file a BPJS Ketenagakerjaan (Social Security for Employment) claim for Gocar drivers who experience work accidents. The research method used in this study is juridical-normative legal research. The data collection method applied in this study involves library research, which includes gathering data from available legal materials in legal literature, regulations, legal journals, books, articles, scholarly opinions, legal cases, jurisprudence, dictionaries, bibliographies, theses, and other materials relevant to the research problem, within the scope of monodisciplinary research. The responsibility of PT Gojek towards Gocar drivers who experience work-related accidents is closely linked to the partnership relationship between Gojek and its drivers, which is not considered an employment relationship due to the absence of the elements of wages and orders.